Examining the impact of dispatch-assisted CPR on bystander CPR performing - Tippayanate, Nantawan; Phonkanya, Patchalee; Neungkantee, Kanokwan; Neungkantee, Kamonchanok; Raksapakdee, Kwansiri; Boonnop, Watcharaporn; Jitsuwan, Natlada (International Journal Of Community Medicine And Public Health, 2024)
Background: Dispatcher-assisted CPR involves emergency medical dispatchers (EMD) delivering real-time CPR instructions to callers during emergencies. This method aims to enable timely bystander CPR before the arrival of emergency medical services, improving survival rates and neurological outcomes of out-of-hospital cardiac arrest (OHCA). This study evaluates the effectiveness of telephone-guided CPR instructions using retrospective audio data. Methods: A retrospective study analyzed OHCA incidents in Mahasarakham, Songkhla, and Prachinburi within a metropolitan EMS system. Audiotapes from emergency calls between January and December 2021 were reviewed. Included were OHCA patients who called the dispatch center and were transported to the hospital by EMS. Exclusions included cardiac arrests in nursing homes, doctors' offices, and jails, as well as cases where EMS witnessed the OHCA or callers initiated CPR before receiving instructions. Results: The study analyzed 280 patients, with 146 callers (52.1%) agreeing to perform CPR. Among the provided DA-CPR instructions, 18 items were significantly associated with bystander CPR performance. Five items that could be omitted to reduce OHCA recognition time delay include the introduction, requesting contact numbers, inquiring about the number of patients, assessing scene safety, and advising tilting the patient in case of vomiting. Conclusions: To reduce the delay in identifying cardiac arrest and promptly initiating chest compressions during OHCA, it is suggested to employ a video call system for early detection of abnormal breathing and unconsciousness. Additionally, integrating automatic geolocation can expedite EMS response.